Impact of Periodontitis and Oral Dysbiosis Metabolites in the Modulation of Accelerating Ageing and Human Senescence - Mariacristina Amato; Alessandro Polizzi; Gaia Viglianisi; Francesco Leonforte; Marco Mascitti; Gaetano Isola (Metabolites)
Periodontitis, a chronic multifactorial inflammatory condition of the periodontium, is originated by a dysbiotic oral microbiota and is negatively correlated with several systemic diseases. The low-chronic burden of gingival inflammation not only exacerbates periodontitis but also predisposes individuals to a spectrum of age-related conditions, including cardiovascular diseases, neurodegenerative disorders, and metabolic dysfunction, especially related to ageing. In this regard, over the local periodontal treatment, lifestyle modifications and adjunctive therapies may offer synergistic benefits in ameliorating both oral and systemic health in ageing populations. Elucidating the intricate connections between periodontitis and senescence is important for understanding oral health’s systemic implications for ageing and age-related diseases. Effective management strategies targeting the oral microbiota and senescent pathways may offer novel avenues for promoting healthy ageing and preventing age-related morbidities. This review will analyze the current literature about the intricate interplay between periodontitis, oral dysbiosis, and the processes of senescence, shedding light on their collective impact on the modulation and accelerated ageing and age-related diseases. Lastly, therapeutic strategies targeting periodontitis and oral dysbiosis to mitigate senescence and its associated morbidities will be discussed.